Three-year outcomes of cystotomy and fibrinogen clot removal for diabetic macular edema with subfoveal cystoid macular edema - Hiroko Yamada; Hisanori Imai; Yasuyuki Sotani; Wataru Matsumiya; Akiko Miki; Sentaro Kusuhara; Makoto Nakamura (Scientific Reports)
Abstract Several new surgical techniques for managing refractory diabetic macular edema (DME) have demonstrated favorable short-term outcomes. However, no studies have reported the long-term outcomes of these treatments. This study aimed to evaluate the long-term outcomes of cystotomy for DME retrospectively. Twenty-seven patients (31 eyes; 16 male, 11 female) who underwent cystotomy for DME between January 2015 and April 2019, with a follow-up period of 3 years were included. Statistical analyses involved variables including age, sex, best-corrected visual acuity (BCVA), central macular thickness (CMT), number of treatments (anti-vascular endothelial growth factor, sub-Tenon injection of triamcinolone acetonide, direct photocoagulation for microaneurysms, vitrectomy with internal limiting membrane peeling), number of clinic visits, and DME recurrence. The mean age was 67.2 ± 9.3 years. BCVA (logMAR) and CMT(µm) significantly improved from preoperatively to 3 years postoperatively (P < 0.001). Total treatments significantly decreased from the year before surgery to the third year after surgery (P < 0.001). The mean number of clinic visits significantly decreased from the year before surgery to the third year after surgery (P < 0.001). Fibrinogen clot removal was performed in 14 eyes. and DME recurrence occurred in 12 eyes. Cystotomy may be a viable treatment option for DME.